First successful case of platinum‐based chemotherapy for neuroendocrine prostate cancer with BRCA2 and PTEN alterations. Issue 1 (20th October 2021) - Omura, Minami; Kosaka, Takeo; Aimono, Eriko; Nakamura, Kohei; Hongo, Hiroshi; Mikami, Shuji; Nishihara, Hiroshi; Oya, Mototsugu
Abstract : Introduction: Deoxyribonucleic acid repair gene mutations are now being studied in a variety of solid tumors, with the hope of predicting prognosis, pathogenesis, and treatment outcomes. Case presentation: We report the case of a Japanese patient with advanced castration‐resistant prostate cancer who exhibited a prominent response to platinum therapy and had coexisting BRCA2 and PTEN mutations according to retrospective multigene panel analysis. Conclusion: Through a review of clinical outcomes and genetic/pathologic profiling, the presented case provides insights into future management strategies based on the tumor genetic status.